Compartment Syndrome After Varicose Vein Surgery Evidenced by CT Images. (March 2016) - Wang, Sheng-Min; Kim, Maru
A 21-year-old man developed compartment syndrome after a varicose vein surgery. Because of a lack of appropriate diagnostic apparatus, it was not possible to measure calf pressure. The only diagnostic tool available was computed tomography (CT). With the aid of CT, faster diagnosis of the compartment syndrome was possible, leading to appropriate management. By providing unique CT images of a patient before and after having compartment syndrome and after a fasciotomy, this study could add valuable references for diagnosis of compartment syndrome using CT.